Hydrothermal synthesis of a concentrated and stable dispersion of TiO2 nanoparticles - Souvereyns, B.; Elen, K.; De Dobbelaere, C.; Kelchtermans, A.; Peys, N.; D’Haen, J.; Mertens, M.; Mullens, S.; Van den Rul, H.; Meynen, V.; Cool, P.; Hardy, A.; et al. (Chemical engineering journal (Lausanne, Switzerland : 1996), 2013)
► Two-step, low temperature hydrothermal method. ► Deagglomeration and stabilization of 6nm nanoseeds via hydrothermal treatment. ► Stable dispersion of anatase TiO2 nanoparticles with a zeta potential of −51mV and content of 10wt.%. ► Attractive as coating solution for the deposition of different morphologies of TiO2. A low temperature method for the preparation of an aqueous dispersion of 10wt.% of TiO2 nanoparticles with prolonged stability is presented. This stable, aqueous dispersion is obtained by a two-step, hydrothermal synthesis method using a maximum temperature of 130°C. The hydrothermal treatment of pre-synthesized crystalline nanoparticles results in a colloidal dispersion with minimal particle agglomeration due to the combination of surface modification, pH adjustment and optimized hydrothermal conditions. The presented procedure can be regarded as an alternative and improved method for the dispersion of TiO2 pre-synthesized nanoparticles in an aqueous medium. The stability (sedimentation and particle agglomeration) of the dispersion is investigated by means of zeta potential measurements, evaluation of viscosity in function of time and interaction potential calculations. Transmission Electron Microscopy, X-ray Diffraction and Raman Spectroscopy are used to characterize the structural and chemical features of the TiO2 nanoparticles. The crystalline nanoparticles in dispersion have dimensions<10nm and contain 80% anatase and 20% brookite, according to quantitative XRD analysis. Additionally, the hydrothermal treatment not only stabilized the particles but also increased the crystallinity of the particles in dispersion as a supplemental advantage. Experiments show that this dispersion can be used in combination with various deposition techniques to obtain films with different morphologies.